Analisis Keterlaksanaan Bimbingan Konseling di SMK Negeri 1 Padang Laweh - Apriliana, Yona; Syukur, Yarmis; T, Taufik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Guidance and counseling (BK) services strategically support students’ personal, social, academic, and career development, particularly in Vocational High Schools (SMK). The need for these services is becoming increasingly urgent given the complexity of challenges SMK students face during their educational journey and transition into the workforce. This study examines the implementation of BK services at SMK Negeri 1 Padang Laweh, focusing on four key aspects: program execution, student participation, service methods, and encountered obstacles. A qualitative descriptive approach was employed. Data were collected through in-depth interviews with school counselors, the principal, and student representatives and document analysis of the school's existing BK program. The results indicate that BK services have been carried out through various activities, such as essential services, individual counseling, and classroom guidance. However, the implementation remains suboptimal due to limited student participation, a lack of varied methods, and several significant challenges, including a shortage of BK personnel, inadequate infrastructure, and students’ limited understanding of the function of BK services. These findings highlight the need to improve the quality of BK service implementation through training, strengthened policy support, and more representative facilities to ensure that BK functions can be carried out more effectively and sustainably.